Green transformational leadership and green creativity? The mediating role of green thinking and green organizational identity in SMEs - Al-Ghazali, Basheer M.; Gelaidan, Hamid Mahmood; Shah, Syed Haider Ali; Amjad, Rafia (Frontiers in Psychology, 2022)
For countries and organizations to achieve sustainable development, radical green creativity is required. Despite the fact that the influencing elements of green creativity have received a lot of attention, there is a little research on the antecedents of green creativity. The current study attempted to fill the gap by exploring the underlying mechanism of green thinking and green organizational identity as mediators. This study aimed to examine the impact of green transformational leadership on green creativity through mediators such as green thinking and creative organizational identity in SMEs. We gathered data from 460 respondents from SMEs operating in Pakistan using a survey questionnaire. The findings revealed that Green transformational leadership had a significant impact on green organizational identity, which cultivated the green creativity in the SMEs. Additionally, results portrayed that green organizational identity performed mediation in the relationship between green transformational leadership and green creativity. Moreover, Green thinking mediate the association green transformational leadership and green creativity. This study offers novel insights of how to stimulate green transformational leadership and cognitive processes in SMEs to encourage green Creativity. The implications for management and practitioners are discussed in light of the study's findings.